Cord blood-derived CD34(+) hematopoietic cells with low mitochondrial mass are enriched in hematopoietic repopulating stem cell function - Romero-Moya, Damia (Ferrata Storti Foundation, 2013)
The homeostasis of the hematopoietic stem/progenitor cell pool relies on a fine-tuned balance between self-renewal, differentiation and proliferation. Recent studies have proposed that mitochondria regulate these processes. Although recent work has contributed to understanding the role of mitochondria during stem cell differentiation, it remains unclear whether the mitochondrial content/function affects human hematopoietic stem versus progenitor function. We found that mitochondrial mass correlates strongly with mitochondrial membrane potential in CD34(+) hematopoietic stem/progenitor cells. We, therefore, sorted cord blood CD34(+) cells on the basis of their mitochondrial mass and analyzed the in vitro homeostasis and clonogenic potential as well as the in vivo repopulating potential of CD34(+) cells with high (CD34(+) Mito(High)) versus low (CD34(+) Mito(Low)) mitochondrial mass. The CD34(+) Mito(Low) fraction contained 6-fold more CD34(+)CD38(−) primitive cells and was enriched in hematopoietic stem cell function, as demonstrated by its significantly greater hematopoietic reconstitution potential in immuno-deficient mice. In contrast, the CD34(+) Mito(High) fraction was more enriched in hematopoietic progenitor function with higher in vitro clonogenic capacity. In vitro differentiation of CD34(+) Mito(Low) cells was significantly delayed as compared to that of CD34(+) Mito(High) cells. The eventual complete differentiation of CD34(+) Mito(Low) cells, which coincided with a robust expansion of the CD34(−) differentiated progeny, was accompanied by mitochondrial adaptation, as shown by significant increases in ATP production and expression of the mitochondrial genes ND1 and COX2. In conclusion, cord blood CD34(+) cells with low levels of mitochondrial mass are enriched in hematopoietic repopulating stem cell function whereas high levels of mitochondrial mass identify hematopoietic progenitors. A mitochondrial response underlies hematopoietic stem/progenitor cell differentiation and proliferation of lineage-committed CD34(−) cells.